2014
DOI: 10.1021/am500769k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEDOT Nanofibril Networks on the Conductivity, Flexibility, and Coatability of PEDOT:PSS Films

Abstract: The use of poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) in electrodes and electrical circuits presents a number of challenges that are yet to be overcome, foremost amongst which are its relatively low conductivity, low coatability on hydrophobic substrates, and decreased conductivity at large strains. With this in mind, this study suggests a simple way to simultaneously address all of these issues through the addition of a small amount of a nonionic surfactant (Triton X-100) to commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
151
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(159 citation statements)
references
References 39 publications
7
151
1
Order By: Relevance
“…The adding of 5 wt.% EG into the pristine PH1000 solution leads to slight reduction of PEDOT:PSS film thickness [24]. The posttreatment of sulfuric acid reduces the thickness from 113 (PH1000-p film) to 57 nm (PH1000-SA) because of the removal of the PSS, which is also consistent with the report in literature [25][26].…”
Section: Fabrication and Characterization Of Solar Cellssupporting
confidence: 89%
“…The adding of 5 wt.% EG into the pristine PH1000 solution leads to slight reduction of PEDOT:PSS film thickness [24]. The posttreatment of sulfuric acid reduces the thickness from 113 (PH1000-p film) to 57 nm (PH1000-SA) because of the removal of the PSS, which is also consistent with the report in literature [25][26].…”
Section: Fabrication and Characterization Of Solar Cellssupporting
confidence: 89%
“…[93][94][95][96][97][98] PEG is a watersoluble polymer and possesses excellent fi lm forming, emulsifying, and adhesive properties. Wang et al [ 93 ] systematically investigated the effect of PEG with different concentrations and molecular weights on the conductivity of PEDOT:PSS, and found that the conductivity of PEDOT:PSS/PEG hybrid fi lms was enhanced compared to the PEDOT:PSS pristine fi lm.…”
Section: Surfactant Treatmentmentioning
confidence: 99%
“…Phase-inducing additives such as dimethyl sulfoxide, 137,138 ethylene glycol 139,140 and fluorosurfactants 141,142 are known to improve electrical properties by creating larger domains for charge transport. Insulating additives such as block copolymer surfactants 60 and crosslinking agents, 126 lower electrical performance.…”
Section: Additives and Modifiersmentioning
confidence: 99%